Determination of As(III) and As(V) in the Wells of the arsenic removal plants in Costa Rica - Arias-Barrantes, Betzabel (2018)
Separation and quantification of soluble and particulate arsenic and As(III) and As (V) were carried out in the wells of six arsenic removal plants operated by AyA in Guanacaste and Alajuela: Bebedero de Cañas, Montenegro and Agua Caliente, Falconiana and Quintas Don Miguel in Bagaces and Santa Cecilia de El Amparo and Cristo Rey in Los Chiles. Inductively coupled plasma mass spectrometry and anion exchange chromatography with Dowex 1-X8 resin were used for this analysis. The methodology was validated, obtaining the following figures of merit: detection limit 0,1 μg/L, quantification limit 0,2 μg/L, veracity as recoveries of different fractions and mixtures between (97-104)%, with variation coefficient between (0,9-12,8)%, as well as repeatability 0,2 % and intermediate repeatability of 0,3 % (n=7). Eight samples were taken monthly wich indicated that in the six wells soluble arsenic prevails on the particulate arsenic. On the other hand, in all the Guanacaste wells and in Cristo Rey de Los Chiles predominates As(V) than As(III), As(III) being undetectable, detectable or in concentrations slightly higher than quantification limit. In the case of Santa Cecilia de El Amparo, there is a mixture of As(III) and As(V) in very similar proportion and predominating one over another depending on the sampling. In addition, this well has the lowest concentration of dissolved oxygen (1,5 mg/L), whereas the remaining wells present higher concentrations.